Unlocking English Vocabulary with “Frozen II”: Exploring Students’ Perception of Animated Movies in Language Learning - Nurul Humairo; Saadillah Saadillah (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2024)
The purpose of this study is to ascertain how students feel about using the animated film Frozen II to increase their vocabulary. Narrative inquiry is used in the study. Ten participants are from the Faculty Tarbiyah and Teacher Training's English Language Education Department. Interview guidelines were used to gather data, and narrative analysis was used for analysis. According to the study's findings, there are three different aspects of perception. 1) cognitive aspect: pupils mostly base their perceptions on what they already know, which facilitates the use of the animated film Frozen II to increase vocabulary in English; 2) affective aspect, in which pupils mostly experience joy when utilizing the animated film Frozen II as a tool to enhance their vocabulary in English; 3) conative aspect: Students demonstrate their opinions through an action, such as being more eager to use the animated film Frozen II to expand their vocabulary in English. Then, there are benefits and drawbacks of using the animated film Frozen II to increase vocabulary in English. The study promotes the use of multimedia tools more widely to establish more dynamic, inclusive, and productive language-learning settings.